Menyelesaikan Pekerjaan Tuhan Berdasarkan Yohanes 4: 34 - Iwan Setiawan; Elisabeth Ngana Hama Ayli; Chresty Thessy Tupamahu; Elri Masniari Saragih; Risart Pelamonia (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
Completing His work is the duty of every believer who serves God with the main task of preaching the gospel of the Kingdom of God. The fact is that there are still believers who serve God without having the right understanding and motivation, one of which is only to pursue material things. As a result, many believers specifically those who are called to be servants of God resign or quit the ministry for worldly reasons. The purpose of this research is to find out the meaning, methods, and authority in 'finishing God's work' according to John 4: 34 so that believers who are called as servants of God have the right understanding and view and are able to implement it in real life. The method used is a qualitative method that focuses on a literature review. The results of the study are: First, the meaning of completing His work is a perfect act that has been carried out by the Lord Jesus, but continues, so that Jesus wants His work to be done by every believer with confidence and sincerity. Second, the way to accomplish His work is to do His will, by bringing souls to God. Third, the authority to complete His work only from God who sent.